Towards an infrastructure to support big data for a smart city project - Gomes E. (2016)
© 2016 IEEE.The spread of projects focused on smart cities have grown in recent years. With this, the massive amount of data generated in these initiatives, creates a degree of complexity in how to manage all this information. In this paper we propose an infrastructure model for big data for a smart city projet. The goal of this model is to present the stages for the processing of data in the step of extraction, storage, processing and visualization, as well as the types of tools needed for each phase. To implement our proposed model, we used the Particip ACT Brazil a project based in smart cities. This project uses different databases to compose its big data and uses this data to seek solutions to urban problems. We observe that our model provides a structured vision of the software to be used in big data server of ParticipACT Brazil. In addition, we can also note that our model can be used in other big data servers.